'Butt shakers' versus national ballet: dancing national identity during the one-party rule in Gabon (1968–1990). Issue 1 (2nd January 2019) - Aterianus-Owanga, Alice
Abstract : This paper sheds light on an unsung part of Gabonese history: the construction of national performance and 'spectacle' culture. It is based on long-term ethnographic and historical research on Gabonese music and dance groups and on an analysis of two music and dance genres created during the one-party rule. While the first one (cultural animation groups) has represented a national unity project and a masculine dominance of the state in a period of 'Renovation', the second (the National Ballet) has used local initiation rituals on stage as emblems of the Nation in a period of heritage-making and the construction of cultural policies. This paper shows how, in the case of Gabon, dance and music ensembles have not only been used by the single party to produce ordinary consent; they were also employed by popular classes to assert their agency, despite the domination of the single party. It highlights how the micropolitics and negotiations of some have shaped local 'traditions' to become part of a 'national culture' in public performances. This unknown history of two national dance and music genres ultimately adds innovative elements to the existing literature on culture, politics, gender, and initiation societies in Gabon.